How much should society fuel the greed of innovators? On the relations between appropriability, opportunities and rates of innovation - Giovanni Dosi; Luigi Marengo; Corrado Pasquali (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
The paper attempts a critical assessment of both the theory and the empirical evidence on the role of appropriability and in particular of Intellectual Property Right (IPR) as incentives for technological innovation. We start with a critical discussion of the standard justification of the attribution of IPR in terms of market failures in knowledge generation. Such an approach we argue misses important features of technological knowledge and also neglects the importance of non-market institutions in the innovation process. Next, we examine the recent changes in the IPR regimes and their influence upon both rates of patenting and underlying rates of innovation. The evidence broadly suggests that, first, IPRs are not the most important device apt to profit from innovation; and second, they have at best no impact, or possibly even a negative impact on the underlying rates of innovation. Rather, we argued, technology- and industry-specific patterns of innovation are primarily driven by the opportunities associated with each technological paradigm. Conversely, firm-specific abilities to seize them and profit from innovation depend partly on adequacy of the strategic combinations identified by the taxonomy of Teece (1986) and partly on idiosyncratic capabilities embodied in the various firms.
Keywords: 330; Innovation; Immaterialgüterrechte; Patent; Marktversagen; Theorie